Comprehensive LET reviewer based on NCBTS and Table of Specifications (TOS) : general education : BEEd and BSEd. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2011)
This LET Reviewer is prepared to help you pass the LET.
English -- Filipino -- Mathematics -- Science -- Social sciences -- Information and communication technology.
Keywords: LICENSURE EXAMINATION FOR TEACHERS (LET) -- REVIEWS, EXERCISE, ETC -- PHILIPPINES